The Persistent and Exceptional Intensity of American Religion: A Response to Recent Research - Landon Schnabel; Sean Bock (Sociological Science, 2017)
Recent research argues that the United States is secularizing, that this religious change is consistent with the secularization thesis, and that American religion is not exceptional. But we show that rather than religion fading into irrelevance as the secularization thesis would suggest, intense religion—strong affiliation, very frequent practice, literalism, and evangelicalism—is persistent and, in fact, only moderate religion is on the decline in the United States. We also show that in comparable countries, intense religion is on the decline or already at very low levels. Therefore, the intensity of American religion is actually becoming more exceptional over time. We conclude that intense religion in the United States is persistent and exceptional in ways that do not fit the secularization thesis.